Framework of Distributed Automated System Controlling Via Mobile Device - Phua, Ging Sheng; Tay, Choo Chuan; Ibrahim, Zulkifilie (2012)
A daily used technology, mobile device such as smartphone has grown its popularity among consumer market and its wide market makes it a candidate for industrial application. Currently, there are no devices based solutions for real time distributed control system via smartphone especially in industrial automation domain. This research has been done on creating framework of distributed controlling via mobile device.